The emerging role of human transmembrane RGD-based counter-receptors of integrins in health and disease - Cabañas, Carlos; Rossi, Elisa; Bartolomé, Ruben A.; Doberstein, Kai; Altevogt, Peter; Casal, J. Ignacio; Bernabeu, Carmelo (Cellular & molecular biology letters, 2025)
Most of the canonical Arg-Gly-Asp (RGD)-containing integrin ligands are extracellular matrix proteins, such as fibronectin, vitronectin and fibrinogen, which regulate cell-ECM adhesion processes. However, during the last years, several reports have demonstrated the existence of non-canonical RGD-containing integrin ligands that are cell surface transmembrane proteins. At variance with the canonical extracellular matrix integrin ligands, the RGD-containing cell surface integrin ligands are involved in cell-cell adhesion processes and function as “integrin counter-receptors”. We propose in this review grouping these transmembrane proteins, which include endoglin, cadherin-5, cadherin-6, cadherin-17, ADAM15, and L1CAM, under the newly coined acronym RGD-ICRs (RGD-containing Integrin Counter-Receptors). We present and discuss the structure of RGD-ICRs, their RGD-based interactions with integrins, the specific signaling pathways triggered in different cell types, as well as their pathophysiological involvement. It can be postulated that RGD-ICRs constitute an emerging group of non-canonical RGD-based integrin counter-receptors. In spite of being encoded by different and independent genes and involved in different pathophysiological processes, all of them appear to have undergone a strong evolutionary convergence in order to acquire the same functional capacity to bind integrins via the RGD motif. Importantly, these RGD-ICRs are also emerging as novel biomarkers and therapeutic targets, with promising clinical potential in a wide array of pathologies.